FACTORS INFLUENCING INTENTION TO VISIT SOUTH KOREA DURING THE PANDEMIC - Andena Noviyati Nabila; Ratna Asih Asih; Salsabila Putri Ramadhanti; Fakhrunnisa Fakhrunnisa; Usep Suhud (Universitas Terbuka, 2021)
This study examines the factors that influence the intention to visit South Korea during the pandemic. This study uses six measured variables: perceived benefits, destination image, e-word of mouth, destination service quality, culture, and visit intention. This study used a quantitative model by collecting data using an online questionnaire and with the criteria for female or male respondents aged 25 years and over and visiting South Korea during the pandemic. The data collection was carried out in January 2021. The total respondents in this study were 212 people consisting of 45 men and 167 women. The results obtained from this study, namely destination service quality has a positive effect on e-word of mouth, e-word of mouth has a positive impact on destination image.